THE CONSTITUTIONAL RIGHT OF ACCESS TO SOCIAL SECURITY: PART II  PROPOSED SOLUTIONS - Avinash Govindjee (Obiter, 2023)
This is the second of two articles dealing with the constitutional right to have access to social security in South Africa. Part I dealt with the general introduction to the topic and highlighted some concerns relating to the right to have access to social security in South Africa and the inclusion of this right in the Constitution. Part II contains a study of various proposed solutions to these problems with particular emphasis on attempts to assist those excluded from the formal framework of social security.